GERAKAN KHARISMATIK DAN SUMBANGANNYA BAGI GEREJA KATOLIK ROMA - Silvester Manca (STIPAS St. Sirilus Ruteng, 2014)
Charismatic movement in the catholic Church has been known as a legal spiritual organization.The authos is more than convinced that this movement has renewed the Church in certain cardinal points as